1985
DOI: 10.1007/bf00044777
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological adaptations of coastal halophytes from foredunes and salt marshes

Abstract: Ecophysiological strategies of coastal halophytes from foredunes and salt marshes are discussed. A comparison is made of the factors that limit growth in salt marshes and sand dunes. In salt marshes, zonation and succession are primarily governed by variation in soil salinity, which strongly depends on inundation with seawater. Results are described of experiments which aim at separating salinity and inundation effects on growth, osmotic and mineral relations in a comparison of salt-marsh halophytes. The growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
62
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(66 citation statements)
references
References 58 publications
0
62
1
Order By: Relevance
“…Plants that inhabit areas where contact with salt is unavoidable, either through saline surface waters or sea spray, tend to be more tolerant to salt. While studies on dune plants have reported elevated leaf necrosis, reduced growth, and diminished reproductive capacities attributed to salt spray, the extent of injuries and the rates of mortality are substantially lower than inland plant species (Rozema et al 1985;Sykes and Wilson 1988;Cheplick and Demetri 1999). Our results are in contrast with studies that have shown decreased growth in S. alterniflora with elevated surface-and soil-water salinities (Mooring et al 1971;Longstreth and Strain 1977;Vasquez et al 2006).…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Plants that inhabit areas where contact with salt is unavoidable, either through saline surface waters or sea spray, tend to be more tolerant to salt. While studies on dune plants have reported elevated leaf necrosis, reduced growth, and diminished reproductive capacities attributed to salt spray, the extent of injuries and the rates of mortality are substantially lower than inland plant species (Rozema et al 1985;Sykes and Wilson 1988;Cheplick and Demetri 1999). Our results are in contrast with studies that have shown decreased growth in S. alterniflora with elevated surface-and soil-water salinities (Mooring et al 1971;Longstreth and Strain 1977;Vasquez et al 2006).…”
Section: Discussioncontrasting
confidence: 84%
“…After 4 weeks of treatment, both Ψ leaf and Ψ xylem decreased due to foliar applications of salt. Lowering of Ψ is frequently observed in coastal plants when challenged by high salinities (Longstreth and Strain 1977;Rozema et al 1985;Hester et al 2001) and are often attributed to accumulations of vacuolar ions and/or the production of cytosolic organic compounds (compatible solutes ;Zhu 2001;Flowers and Colmer 2008). Although S. alterniflora can maintain some control over ion uptake from seawater, perhaps including selective uptake of K + over Na + , buildup of Na + does occur in shoot tissues (Smart and Barko 1980;Bradley and Morris 1991;Vasquez Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations